2019
DOI: 10.1111/pirs.12468
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits, migration intentions, and cultural distance

Abstract: This paper investigates the relationship between Big Five personality traits and individuals' intentions to migrate in countries that vary in their culture. Using data collected from university students in Germany, we find that extraversion and openness are positively associated with migration intentions, while agreeableness, conscientiousness, and emotional stability negatively relate to migration intentions.Openness positively and extraversion negatively relate to the willingness to move to culturally distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 74 publications
(130 reference statements)
0
37
1
3
Order By: Relevance
“…Different studies have investigated this phenomenon in contemporary populations. Fouarge et al investigated the relationship between the big personality traits and individuals’ migration intentions and found that extraversion positively associates with the intention to migrate [ 27 ]. This underlies that psychic costs associated with migration differ across individuals as their personality traits affect how much they perceive these costs under an environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have investigated this phenomenon in contemporary populations. Fouarge et al investigated the relationship between the big personality traits and individuals’ migration intentions and found that extraversion positively associates with the intention to migrate [ 27 ]. This underlies that psychic costs associated with migration differ across individuals as their personality traits affect how much they perceive these costs under an environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies by Teichert et al 2018, Hooijen et al (2017) and Imeraj et al (2017) point to components other than economic factors, such as how long one has been living in an area, the importance of familiarity with the region, the quality of life, and social networks underlying spatial mobility, or the intention to be spatially mobile. In addition, Fouarge et al (2019) study the intention to emigrate after graduation, using a German sample that takes into account the role of personality traits. They find that students scoring high on openness to experience and extraversion are more likely to have the intention to emigrate after graduation, in contrast to more conscientious and agreeable students.…”
Section: Settlement Behaviour Among Recent Graduatesmentioning
confidence: 99%
“…This result is in line with the features of agreeableness, since they convey friendly, trusting, and kind personalities (Ashton, 2007). Lastly, high scorers on agreeableness tend to be less geographically mobile ( Fouarge et al, 2019;Rentfrow & Jokela, 2016;Jokela, 2009). characteristics, such as being organized, efficient, self-disciplined, and compliant (Ashton, 2007).…”
Section: Environmental Characteristics and Their Relationship With Pementioning
confidence: 99%
See 2 more Smart Citations